Tumor-Infiltrating PD-L1+ Neutrophils Induced by GM-CSF Suppress T Cell Function in Laryngeal Squamous Cell Carcinoma and Predict Unfavorable Prognosis - Tang D; Zhang D; Heng Y; Zhu XK; Lin HQ; Zhou J; Tao L; Lu LM (Dove Medical Press, 2022)
Di Tang,1,* Duo Zhang,1,* Yu Heng,1 Xiao-Ke Zhu,1 Han-Qing Lin,1 Jian Zhou,1 Lei Tao,1 Li-Ming Lu2 1Department of Otorhinolaryngology and ENT Institute, Eye & ENT Hospital, Fudan University, Shanghai, People's Republic of China; 2Shanghai Institute of Immunology, Shanghai Jiaotong University School of Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Li-Ming Lu, Shanghai Institute of Immunology, Shanghai Jiaotong University School of Medicine, 280 South Chongqing Road, Shanghai, 200025, People's Republic of China, Tel +86-13916235624, Fax +86-021-63846383, Email lulunew2003@163.com Lei Tao, ENT Institute and Department of Otorhinolaryngology, Eye & ENT Hospital, Fudan University, 83 Fenyang Road, Shanghai, 200031, People's Republic of China, Tel +86-13916944810, Email doctortaolei@163.comPurpose: Chronic inflammation contributes to tumor initiation, progression, and immune escape. Neutrophils are the major component of inflammatory response and participate in the tumorigenesis process. However, compared to other immune cells in the tumor microenvironment of laryngeal squamous cell carcinoma (LSCC), neutrophils, especially the tumor-associated neutrophils (TANs), have not yet been comprehensively explored. The mechanism for regulating the crosstalk between TANs and tumor cells still remains unclear.Materials and Methods: The distribution profiles and phenotypic features of neutrophils and other inflammatory immune cell populations from a large LSCC patient cohort were systemically analyzed. Co-culturing of peripheral blood associated neutrophils (PANs) and TANs with PBMCs was performed, and the immunosuppression effect on T-cells was examined.Results: LSCC microenvironment is highly inflammatory with remarkable TANs infiltration, which is often associated with unfavorable prognosis and advanced clinical stage. We find that TANs in LSCC display morphologically immature and lower apoptosis, exhibit distinctively immunosuppressive phenotype of high PD-L1, and suppress CD8+ T lymphocytes proliferation and activation. We subsequently discover that PD-L1+TANs induced by LSCC-derived GM-CSF potently impair CD8+ T-cells proliferation and cytokines production function, which are partially blocked by a PD-L1-neutralizing antibody. Clinical data further support GM-CSF as an unfavorable prognostic biomarker and reveal a potential association with inflammatory immune cell infiltration, in particular neutrophils.Conclusion: Tumor-infiltrating PD-L1+ neutrophils induced by LSCC-derived GM-CSF suppress T cell proliferation and activation in the inflammatory microenvironment of LSCC and predict unfavorable prognosis. These TANs cripple antitumor T cell immunity and promote tumor progression. Our findings provide a basis for targeting PD-L1+TANs or GM-CSF as a new immunotherapeutic strategy for LSCC.Keywords: laryngeal squamous cell carcinoma, LSCC, tumor-associated neutrophils, TANs, PD-L1, inflammatory microenvironment, immune suppression, granulocyte-macrophage colony stimulating factor, GM-CSF